Analysis of the Among System-Based Discovery and Inquiry Learning Models - Neni Hermita; Zetra Hainul Putra; Jesi Alexander Alim; Mike Fitriani; Dewi Nasien; Khoiro Mahbubah (Journal Of Teaching And Learning In Elementary Education, 2022)
This study compares the syntax of the discovery learning and inquiry learning models based on the Among system. This research was a descriptive type of research and used a comparative design. The method of data collection in this research was a literature study. The literature study used is research that is in accordance with the research of researchers and the latest research. The results found that the learning model of discovery learning and inquiry learning based from the Among system was very well implemented in elementary schools. The use of these various models can be adapted to the needs of the educator. Along with the literature study, these two models can support students' abilities and create meaningful learning for students.